Farmers’ demand for quality and nutritionally enhanced sweetpotato planting material: Evidence from experimental auctions in Rwanda - Okumu, B.; Rajendran, S.; Okello, J.J.; Maredia, M.; Ward, Patrick S.; Gatto, M.; Nshimiyimana, J.; Kilwinger, F.; Sindi, K.; David, S. (2024)
In sub-Saharan Africa, most farmers source sweetpotato vines from neighboring farmers or their plots during the previous season. However, in the absence of “clean” vines produced with good agricultural 13 practices, farmer-to-farmer vine exchanges and own-saved vines tend to encourage the accumulation of pests and diseases that ultimately affect yields. Despite this, the demand for nutritionally rich variety and biofortified crop orange-fleshed sweetpotato (OFSP) is limited due to farmers’ unfamiliarity with the product and its novel attributes. In this study, we investigate demand for quality sweetpotato vine and 17 nutritional attributes of the crop using a second price experimental auction approach to determine the 18 premium price, farmers are willing to pay for these attributes and investigate drivers of market demand. 19 The study revealed that in the absence of information on the source of vines, maturity and resistance to 20 diseases, farmers are willing to pay a premium of about 35 Rwandan Francs for high-quality vines sourced 21 from the trained seed multipliers. However, with the provision of information on the source of vines, 22 maturity, and resistance to diseases of the vines, the premium price increases significantly to 133.71 23 Rwandan francs and to 107.22 Rwandan Francs after the provision of visual information depicting the 24 performance of the vines in demonstration plots. The premium price also increases significantly for vines 25 sourced from neighbors to about 74.35 Rwandan francs, which further increases to 151.53 Rwandan francs 26 when nutrition information is provided to the farmers. It is therefore evident that the provision of 27 information and demonstration of the performance of the crops is important for the adoption of improved 28 variety and increases the effective demand.